Mass Spectrometry-Based Proteomics Technologies to Define Endogenous Protein-Protein Interactions and Their Applications to Cancer and Viral Infectious Diseases - Yu, Clinton; Adavikolanu, Rithika; Kaake, Robyn M; Huang, Lan (Mass spectrometry reviews, 2025)
An intricate network of protein assemblies and protein-protein interactions (PPIs) underlies nearly every biological process in living systems. The organization of these cellular networks is highly dynamic and intimately tied to the genomic and proteomic landscapes of a cell. Disruptions in normal PPIs can impair cellular functions and contribute to the development of human diseases. In recent years, targeting PPIs has emerged as an attractive strategy for drug discovery. Consequently, the identification and characterization of endogenous PPIs-those occurring naturally under physiological conditions-has become crucial for unraveling the molecular mechanisms driving human pathology and for laying the groundwork for novel diagnostics and therapeutics. Owing to numerous technological advancements, mass spectrometry (MS)-based proteomics has transformed the study of PPIs at the systems-level. This review focuses on proteomics approaches that enable the characterization of physiologically relevant endogenous interactions, spanning complex-centric to structure-centric analyses. Additionally, their applications to define native PPIs in the contexts of cancer and viral infectious diseases is highlighted.